Public spaces critical issues analysis for soft mobility: A methodology for the cognitive framework definition - Boglietti, Stefania; Tiboni, Michela (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Over time, one of the causes that led to the progressive reduction in the public space quality is the massive diffusion of private cars. The characteristics of quality, safety, and accessibility should be indispensable for the public space, and these needs should be met through targeted interventions, with particular attention to the integration between urban planning and mobility. Therefore, in this article, we study the public spaces criticalities to promote soft mobility. A methodology is proposed for the definition of the public spaces’ cognitive framework. The methodology is based on three different phases: the urban context analysis, the analysis of the perception of space by the user, and some preparatory solutions for the subsequent design phase. Technical analyzes are based on on-site observations, measurements, data processing, and thematic maps. On the contrary, the perception phase is based on the direct involvement of citizens through a survey. The methodology is applied to the case study of the San Bartolomeo and Casazza districts of the city of Brescia. The results show a strong connection between the urban spaces geometric characteristics and their perception by users, useful for the design of a public space weighted to the needs encountered.